A qualitative holographic study of hemipelvic and acetabular deformation caused by different hip prostheses - Spirakis, Athanasios Apostolou (Division of Biomedical Engineering, 2017)
Aseptic loosening of the components is probably the most common long-term complication resulting in failure of Total Hip Arthroplasty. The mechanical behaviour of bone under load is one of the contributory causes of loosening encountered at the prosthesis/cement/bone interface. The present study dealt with a series of invitro experiments conducted on epoxy resin models of human hemi-pelves with different commercially available acetabular components implanted in them. These are used for the construction of simplified models of the artificial hip joint (three-dimensional) and of the prosthesis/cement/bone acetabular interface (two-dimensional). Loading conditions for the models included tensioning of the simulated abductor muscles for the hemi-pelvic and femoral loading for the prosthesis/cement/bone interface study. The experimental method employed was real-time holographic interferometry, a stress analysis technique recently used in the biomechanical field, which permitted whole-field simultaneously inspection of deformation patterns. The holographic interferograms were interpreted in a qualitative rather than a quantitative manner. The models do not exactly represent the in-vivo situation. Since this study identified high stresses both in the hip bone as well as in the interface (prosthesis/bone) it is suggested that these stresses are implicated in the mechanical pathogenesis of loosening. The observed changes in stress levels detected in our models could serve as a guide for future designs of acetabular prostheses as well as guide a in surgical techniques.